Hydrogen Sulfide Inhibits L-Type Calcium Currents Depending upon the Protein Sulfhydryl State in Rat Cardiomyocytes - Zhang, Rongyuan (Public Library of Science, 2012)
Hydrogen sulfide (H(2)S) is a novel gasotransmitter that inhibits L-type calcium currents (I (Ca, L)). However, the underlying molecular mechanisms are unclear. In particular, the targeting site in the L-type calcium channel where H(2)S functions remains unknown. The study was designed to investigate if the sulfhydryl group could be the possible targeting site in the L-type calcium channel in rat cardiomyocytes. Cardiac function was measured in isolated perfused rat hearts. The L-type calcium currents were recorded by using a whole cell voltage clamp technique on the isolated cardiomyocytes. The L-type calcium channel containing free sulfhydryl groups in H9C2 cells were measured by using Western blot. The results showed that sodium hydrosulfide (NaHS, an H(2)S donor) produced a negative inotropic effect on cardiac function, which could be partly inhibited by the oxidant sulfhydryl modifier diamide (DM). H(2)S donor inhibited the peak amplitude of I( Ca, L) in a concentration-dependent manner. However, dithiothreitol (DTT), a reducing sulfhydryl modifier markedly reversed the H(2)S donor-induced inhibition of I (Ca, L) in cardiomyocytes. In contrast, in the presence of DM, H(2)S donor could not alter cardiac function and L type calcium currents. After the isolated rat heart or the cardiomyocytes were treated with DTT, NaHS could markedly alter cardiac function and L-type calcium currents in cardiomyocytes. Furthermore, NaHS could decrease the functional free sulfhydryl group in the L-type Ca(2+) channel, which could be reversed by thiol reductant, either DTT or reduced glutathione. Therefore, our results suggest that H(2)S might inhibit L-type calcium currents depending on the sulfhydryl group in rat cardiomyocytes.